I cannot figure this out...

Tutors, sign in to answer this question.

Hi Chris,

Assuming you meant:

x/(+2) = (x/3) - 3

or, a little prettier:

<pre>

x x

--- = --- - 3

+2 3

</pre>

(darn, doesn't look like wyzant will let us use html tags)

Then you can subtract x/3 from both sides:

x/2 - x/3 = x/3 -3 - x/3

x/2 - x/3 = -3

Then, get a common denominator:

(x/2)(3/3) - (x/3)(2/2) = -3

3x/6 - 2x/6 = -3

Next, combine like terms (fraction subtraction):

x/6 = -3

Now, multiply both sides by 6:

6(x/6) = (-3)6

x = -18

Hi Chris;

I am certain this is NOT...

x/(+2)=x/(3-3)

because 3-3=0. A numerator cannot be zero.

I think this is...

x/(+2)=(x/3)-3

+2 and 2 is the same thing.

So...

x/2=(x/3)-3

Let's eliminate fractions. 2 x 3 =6. Let's multiply both sides by 6...

6(x/2)=6[(x/3)-3]

3x=2x-18

Let's subtract 2x from both sides as we proceed to isolate x...

-2x+3x=2x-18-2x

x=-18

Let's check our work.

The original question was...

x/(+2)=(x/3)-3

-18/2=(-18/3)-3

-9=-6-3

-9=-9

If I misunderstood the original question, please let me know.

I hope this helps either way.

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.